(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
The University of Pamplona, through its Early Childhood Education program, has been implementing the ZC project, which was presented by the Faculty’s Pedagogy Research Group and approved. For three consecutive years, it has been put into practice in each of the subjects that form part of the curriculum, in order to give young people the opportunity to pursue a career that will lead them to a better life and better performance as professionals. However, very few higher education institutions are applying the government regulations.